Does Shopping Orientation and Gender Different Affect Online Shopping Lifestyle? - Nofirda, Fitri Ayu; Dwita, Vidyarini (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. This study aims to determine the Influence of Shopping Orientation and Gender Different on Online Shopping Lifestyle in Pekanbaru City. This research was conducted in Pekanbaru City with 104 respondents. This study used quantitative methods by drawing research samples using the purposive sampling method. Data testing using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, there are two hypothesis tests and determination tests with the help of SPSS 23 software. The results of this study show that Market Orientation and Gender Different partially affects Online Shopping Lifestyle, Gender Different partially affects Online Shopping Lifestyle, and Shopping Orientation and Gender Different partially affects Online Shopping Lifestyle The findings suggest that market orientation can enhance their position for success by improving their online shopping lifestyle. Overall, this study provides valuable insights into the importance of market orientation in enhancing production performance for manufacturing SMEs, and its implications can be useful for practitioners, policymakers, and scholars interested in ecommerce platform competitiveness. Keywords: Market orientation, shopping orientation, gender different, online shopping lifestyle, e-commerce Abstrak. Penelitian ini bertujuan untuk mengetahui Pengaruh Orientasi Belanja dan Gender Different Terhadap Online Shopping Lifestyle di Kota Pekanbaru. Penelitian ini dilakukan di Kota Pekanbaru dengan jumlah responden 104 orang. Penelitian ini menggunakan metode kuantitatif dengan penarikan sampel penelitian menggunakan metode purposive sampling. Pengujian data menggunakan uji validitas, uji reliabilitas, uji asumsi klasik, uji regresi linear berganda, uji hipotesis dan uji determinasi dengan bantuan software SPSS 23. Hasil penelitian ini menunjukkan bahwa Orientasi Belanja secara parsial berpengaruh terhadap Online Shopping Lifestyle,Gender Different secara parsial berpengaruh terhadap Online Shopping Lifestyle, dan Orientasi Belanja dan Gender Different secara parsial berpengaruh terhadap Online Shopping Lifestyle Kata kunci: Orientasi Pasar, orientasi belanja, perbedaan gender, gaya hidup belanja online, e-commerce